Alkalicky aktivované materiály s urychlenou dobou tuhnutí - Šebek, Pavel (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Práce obsahuje přehled nejčastěji používaných urychlovacích přísad do betonu a mechanismus jejich působení. V praktické části byl zkoušen vliv tří urychlovačů na alkalicky aktivované směsi na bázi metakaolinu a strusky. Oba prekurzory byly aktivovány vodním sklem. Byl posuzován vliv urychlovacích přísad na vlastnosti čerstvé malty i na mechanické vlastnosti zkušebních těles. Jako velmi účinný urychlovač se na základě experimentů jeví vápenný hydrát. Urychlující efekt na tuhnutí geopolymerních past byl pozorován též při použití mayenitu (C12A7). Naopak účinek přirozeného hydraulického vápna byl minimální.

This paper contains an overview of most used accelerating admixtures for concrete and their working mechanism. The effect of three accelerating admixtures on the setting of alkali-activated mixtures based on metakaolin and alkali-activated slag was tested. Both precursors were activated by water glass. The influence of accelerators on pastes in plastic state and on mechanical properties of hardened mortars was observed. The calcium hydrate seems to be a very efficient accelerator based on the results of the experiments conducted. Mayenite (C12A7) was observed to have an accelerating effect on the setting time of geopolymer pastes as well. On the other hand, the accelerating effect of natural hydraulic lime was minimal.
Alkali-Activated Materials with Accelerated Setting Time
Keywords: Geopolymer; alkalicky aktivovaná struska; urychlovací přísady; doba tuhnutí; mechanické vlastnosti; mikrostruktura; Geopolymer; alkali-activated slag; accelerating admixtures; setting time; mechanical properties; microstructure